3D interactions for a virtual museum - Quah, David Yew Seng (Nanyang Technological University, 2020)
A 3D virtual museum is a virtual environment created to simulate a museum and to allow a player to walk through it. This project expands upon a previous project of creating a virtual rendition of the Chinese Heritage Centre (CHC) in Nanyang Technological University (NTU). The objective of this project is to implement Virtual Reality (VR) functionality into the project and make use of the advantages that VR gives to make the experience more immersive and interesting for the player. The project consists of 2 main sections. The first section deals with the implementation of VR as well as how the system handles events generated by the VR controllers. It also covers the changes in the user interface and user experience due to using the new VR technology. The second section evaluates the project in its current state and concludes the report with further improvements that could be implemented to the project. While the current project is useable as a proof of concept it is still in a very early stage of development and many more improvements can be included to give a more immersive experience to the player.